Emerging trends of culturing microalgae for fish‐rearing environment protection. Issue 1 (14th September 2020) - Yang, Limin; Li, Huankai; Lu, Qian; Zhou, Wenguang
Abstract: The application of microalgae biotechnology, which can recover nutrients from wastewater, improve water quality, and feed some aquatic animals, is becoming an emerging trend in the development of eco‐friendly aquaculture. Previous studies explored a variety of models to support the use of microalgae in aquaculture practice, verifying the feasibility and advantages of microalgae‐based aquaculture. However, a couple of bottlenecks and problems jeopardizing the application of microalgae biotechnology in aquaculture are discovered in the research and industrial practice. This work, hence, summarizes the research progress and the current opinions relating with the microalgae‐based aquaculture and proposes some critical thoughts about the bottlenecks challenging its industrial implementation. © 2020 Society of Chemical Industry (SCI)